REINREF - the datafile for literature about reindeer and reindeer husbandry - Skjenneberg (ed.), Sven (Rangifer, 1987)
The datafile is established at the library at Skogshögskolan, Umeå, Sweden (The Swedish University of Agriculture, Department of Forestry).